Computer Assisted Immunohistochemical Score Prediction Via Simplified Image Acquisition Technique - Jawad, Salam N; Abdullah, Bashar H (Journal of Baghdad College of Dentistry, 2017)
Background: techniques of image analysis have been used extensively to minimize interobserver variation of immunohistochemical scoring, yet; image acquisition procedures are often demanding, expensive and laborious. This study aims to assess the validity of image analysis to predict human observerâ€™s score with a simplified image acquisition technique. Materials and methods: formalin fixed- paraffin embedded tissue sections for ameloblastomas and basal cell carcinomas were immunohistochemically stained with monoclonal antibodies to MMP-2 and MMP-9. The extent of antibody positivity was quantified using ImagejÂ® based application on low power photomicrographs obtained with a conventional camera. Results of the software were employed to predict human visual scoring results with stepwise multiple regression analysis. Results: the overall prediction of epithelial score depicted as r square value was 0.26 (p<0.001) which was obviously higher than that of stromal score (0.10; p<0.01). Epithelial and stromal MMP-2 score prediction was generally higher than that of MMP-9. Collectively, ameloblastomas had a more efficient score prediction compared to basal cell carcinomas. Conclusion: there is a considerable variability in the prediction capacity of the technique with respect to different antibodies, different tumors and cellular versus stromal score.